Landscape models and magnetic susceptibility on soil identification and characterization - Matias, Sammy Sidney Rocha (2013)
The detailed knowledge of soils and their attributes, across the landscape, is a permanent demand of urban and agro-industrial systems, for planning their sustainable use and occupation. This study aimed at evaluating the potential of landscape models and the magnetic susceptibility in the identification and characterization of oxisols, in Guariba, São Paulo State, Brazil. A total of 514 soil samples were collected in 110.0 ha, at the depths of 0.0-0.20 m and 0.60-0.80 m. Different landscape compartments, based on the geomorphic surface and segment slope models, were identified. In each landscape compartment, trenches were opened for soil classification. The samples were analyzed for particle size and chemical properties, pH (water, CaCl2 and KCl), organic matter, extractable P, K+, Ca2+, Mg2+ and H+ + Al3+. The contents of SiO2, Al2O3, Fe2O3 and free (Fed) and slightly crystallized (Feo) Fe oxides were determined in samples from the trenches, as well as the magnetic susceptibility (MS). Taxonomically similar soils, but in different landscape compartments, presented different values for the attributes studied, indicating that the landscape models and magnetic susceptibility may be viable, as a field technique, to help detailing the variation of soil attributes. The magnetic susceptibility showed potential for delimiting geomorphic surfaces mapped in the field, emphasizing its potential use for identifying and characterizing homogeneous areas.